Intracameral phenylephrine and ketorolac injection (OMS302) for maintenance of intraoperative pupil diameter and reduction of postoperative pain in intraocular lens replacement with phacoemulsification - Lindstrom RL (Dove Medical Press, 2014)
Richard L Lindstrom,1 James C Loden,2 Thomas R Walters,3 Steven H Dunn,4 J Steven Whitaker,5 Terry Kim,6 Gregory A Demopulos,5 Khiun Tjia7 1Minnesota Eye Consultants, Minneapolis, MN, USA; 2Loden Vision Centers, Goodlettsville, TN, USA; 3Texan Eye Care, Austin, TX, USA; 4Houston Eye Associates, Houston, TX, USA; 5Omeros Corporation, Seattle, WA, USA; 6Duke University Eye Center, Durham, NC, USA; 7Isala Clinics, Zwolle, the Netherlands Background: The purpose of this study was to evaluate the effect of OMS302 on intraoperative pupil diameter and early postoperative ocular pain when administered during intraocular lens replacement surgery.Methods: Four hundred and six patients (406 study eyes; 202 in the OMS302 group and 204 in the placebo group) were entered into this randomized, double-masked, placebo-controlled, multicenter Phase III study, which was conducted at 15 centers in the USA and the Netherlands. The patients received OMS302 (60.75 mM phenylephrine HCl and 11.25 mM ketorolac tromethamine) or placebo in irrigation solution during intraocular lens replacement. No other changes in procedure were required. Coprimary endpoints were change in pupil diameter over time from surgical baseline to end of procedure and patient-reported ocular pain during the first 12 hours postoperatively. Secondary endpoints included additional measures of pupil diameter and postoperative pain. Results: OMS302 was superior to placebo in maintaining intraoperative mydriasis, preventing miosis, and reducing postoperative pain. The weighted mean (standard error) difference (OMS302 – placebo) in change in the area under the curve from baseline for pupil diameter was 0.590 ([0.049]; 95% confidence interval 0.494 to 0.686; P<0.0001). For ocular pain scores, the weighted mean (standard error) difference was –4.580 ([1.192]; 95% confidence interval –6.917 to 2.244; P=0.0002). All secondary efficacy results favored OMS302. Specifically, analyses supporting prevention of miosis (patients with ≥6 mm pupil diameter at completion of cortical clean-up and those with <6 mm diameter at any time during surgery) were significant for OMS302 (95.9% versus 77.0% and 9.2% versus 38.0%, respectively; P<0.0001 for each endpoint). OMS302 was well tolerated and not associated with any unexpected adverse events.Conclusion: OMS302 maintained mydriasis, prevented miosis, and reduced early postoperative pain when administered in irrigation solution during intraocular lens replacement, with a safety profile similar to that of placebo. OMS302 is preservative-free and bisulfite-free, and its administration does not require any modification to the surgical procedure. Keywords: intraocular lens replacement surgery, cataract, mydriasis, miosis, postoperative pain, OMS302